Influence of Psychological Need-Based Teachers’ Autonomy Support on Effectiveness and Engagement in English Learning - Liu, Pengkai (Front Psychol, 2021)
It is to explore the effects of psychological needs and teachers’ autonomy support on students’ English learning, hoping to provide a realistic basis for the innovation of English teaching. Four hypotheses are proposed first, and 420 students are then randomly selected from seven classes in Xi’an Ai Zhi Zhong Xue in Shaanxi Province as the research subjects, with 420 questionnaires distributed. After invalid questionnaires are excluded, a total of 400 valid questionnaires are collected. Then, SPSS26.0 is employed to analyze the collected scale data. The average value of emotional exhaustion and the average value of low sense of achievement are relatively close in the direction of English learning burnout, which are larger than that in the other two directions. The three directions in English learning burnout are positively correlated with each other. The three directions in English learning engagement are positively correlated with those of psychological needs. Besides, there is an obvious positive correlation between the three directions of English learning engagement with teachers’ autonomy support (p < 0.01). However, the three directions in teachers’ autonomy support and the three directions in psychological needs are all negatively correlated with English learning burnout (p < 0.01). To sum up, the psychological needs of middle school students are effectively met, and teachers’ autonomy support can obviously promote the effectiveness and engagement of middle school students’ English learning.